Solidification Effect and Mechanism of Marine Muck Treated with Ionic Soil Stabilizer and Cement - Xue-Ting Wu (MDPI AG, 2021)
In this study, an environmentally friendly ionic soil stabilizer (ISS) was adopted with combination of Portland cement to stabilize a marine muck. The macro and micro tests results demonstrated that the ISS was an effective stabilizer to improve the strength of marine muck when it was used combined with cement after adding the alkalizer NaOH. Except for the reduction in interlayer distance of clay minerals by ISS, Ca<semantics>2+</semantics> and SO<semantics><msubsup>42−</msubsup></semantics> dissolved from ISS promoted the production of ettringite (AFt), pozzolanic and carbonation reactions of Portland cement in the presence of NaOH. Meanwhile, the hydration products of curing reaction notably agglomerated soil particles, which caused an obvious decrease of pores and a high increase of strength for solidified soils. Furthermore, this combination of stabilizers can not only save the dosage of cement, but also accelerate the solidification speed, decrease the cement setting time within 7 days to meet the curing requirements, and enhance the strength of solidified soils.